Impact of Organization’s Prevailing Atmospheric Conditions on Employee’s Stay back or Quit Decisions - Gajendran. A, Megavannan. R, Muthukumar. K (Journal of Informatics Education and Research, 2024)
Employees are the important source for the accomplishment of goals of any business Units. So, it is inevitable for an organization and or managerial personals to retain their talented workforces to attain predetermined standards and to achieve positive outcomes and to realize expected efforts to transform organization to attain growth within a short span of time. But in most of the cases, organizations are unable to retain its employees. On other side, workforces also able to take their own individual decision and decide whether it is possible for them to stay back or quit. In addition, the researchers decided to identify the causes behind employee’s positive and adverse decisions. The authors also feels that this research attempt could give possible ideas and inputs to managerial people to take adequate measures to preserve talented workforce with their organization to achieve its goals. The present research emphases to revelation of various factors which influence employees to make their immediate decision. The aim of this research is to throw light on identifying talented people, motivate them in the right way, and satisfy them to be with organization to make use of their talents and efforts to increase organizational efficiency. This study also helps to suggest research models and measures to establish positive and favorable thoughts among employees to reduce employee turnover and to ensure an intensive motivation system.